Human foraging responses to climate change; Here Sorot Entapa rockshelter on Kisar Island - Kaharudin, Hendri A. F.; Mahirta, Mahirta; Kealy, Shimona; Hawkins, Stuart; Boulanger, Clara; O’Connor, Sue (Wacana, Journal of the Humanities of Indonesia, 2019)
This study explores prehistoric human subsistence adaptations within the context of changing marine and terrestrial environments on the tiny Island of Kisar, beginning during the Pleistocene-Holocene transition around 15,000 years ago (ka). We use zooarchaeological data on faunal remains (vertebrates and invertebrates) recovered from Here Sorot Entapa rockshelter (HSE) in temporal relationship to climate data from Flores to document prehistoric human responses to regional sea-level, temperature, and associated habitat changes that occurred after the Last Glacial Maximum (LGM). Human settlement intensity peaked during the colder drier conditions of the Bølling-Allerød period at 14.4-13 ka, and the site was abandoned during a period of unstable sea levels and coastal habitats between 9.4-5 ka. Holocene climate change coincides with increased reefal subsistence, and an increase in crab exploitation over sea urchin use. Rodent abundance increases in the early Holocene, possibly in response to expanding forests during warmer wetter conditions, with a significant increase in the late Holocene as a result of the human introduction of exotic species to the island.